The Power of Power Saving: A Study on Consumers' Awareness, Measures and Attitude towards Electricity Saving - Patel, Rajnikant; Rathod, Raju M. (Indian Journal of Marketing, 2004)
The Universe revolves around energy. Be it the galaxies, stars or even object. Since time immemorial human's first important invention was to create a fire. Fables across the world are abundant with stories of how man came across this fire. Since then we have come a long way indeed. Growth of the infrastructure sectors is a critical pre - requisite for a sustainable growth of the economy. Investments into these sectors have accounted for a major share of the public spending for most of the past fifty years. Adequate, cost - effective and quality infrastructure is crucial for economic growth and development. It also affects international competitiveness and flow of direct international investments. The ongoing economic reforms, thus, attach a high priority to the better utilization of existing infrastructure assets and fresh developments also, in order that existing bottlenecks do not inhibit the overall economic growth and export dynamism.